Physical Activity in Mathematics Education: Developing “Grundvorstellungen” of Multiplication by Learning through Physical Activity - Rottmann, Thomas; Bayer, Friederike (Learning Tech, 2018)
The term “Learning through Physical Activity” is used to describe learning processes in which whole-body movement is strongly linked to the learning content. Although this way of learning is generally accepted and its positive impact on the learning process is theoretically grounded, ideas for the practical application in mathematics education in Germany are largely missing, as is any corresponding scientific research. This paper aims to close this research gap. In order to do so, movement games, which support the development of “Grundvorstellungen” of multiplication, were developed and scientifically evaluated using a pre- and post-test design during a teaching unit in a mixed-age group.